(untitled) (World Economics and Finance Bulletin, 2022)
The aim of the research is to identify the auditor’s responsibility towards discovering the risks of material misrepresentation when auditing in light of the application of International Auditing Standard No. (240), to achieve this goal a questionnaire was designed and distributed to the research sample represented by auditors working in audit companies and offices of the first category who are in the Bulletin of 2022 issued by the Board of Audit and Oversight Profession in Iraq. The research found that there is statistical importance for external auditors in Iraq to realize their responsibilities for detecting fraud from the point of view of the sample members and to adhere to the necessary tests and procedures to identify and assess the risks of fundamental errors when auditing financial statements. The most important recommendations: The necessity for the Council of the Audit and Monitoring Profession in Iraq to obligate the external auditors to follow the audit procedures because of their contribution to strengthening the auditors’ reports, the need for professional organizations to define the responsibilities of external accounts in an accurate and clear manner, while setting the rules and controls related to detecting fraud in the lists Finance